Investigation of Point Merge Utilization Worldwide Using Opensky Network Data - Hardell, Henrik; Polishchuk, Tatiana; Smetanová, Lucie (Journal of Open Aviation Science, 2023)
Point Merge (PM) arrival procedure is implemented at multiple airports around the World. There are different PM design variants: with overlapping, partially overlapping or separated sequencing legs, a position of the sequencing legs inside or outside the TMA, different geometry of the flows to PM or merging to a point; each coming with a different impact on the trade-offs associated with the structure. In this work, we investigate the usage of PM procedures in several airports around the globe using open-access ADS-B-based data provided by the OpenSky Network. We analyse arrival flows at the airports with PM, and propose a catchment algorithm to see which flights from the blend are actually adherent to the procedure. Then quantify the PM utilization by applying the performance indicators specifically designed for this purpose.